2016
DOI: 10.3390/toxins8080238
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Neurotoxin BMAA and Mercury in Sharks

Abstract: Sharks have greater risk for bioaccumulation of marine toxins and mercury (Hg), because they are long-lived predators. Shark fins and cartilage also contain β-N-methylamino-l-alanine (BMAA), a ubiquitous cyanobacterial toxin linked to neurodegenerative diseases. Today, a significant number of shark species have found their way onto the International Union for Conservation of Nature (IUCN) Red List of Threatened Species. Many species of large sharks are threatened with extinction due in part to the growing high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Among marine taxa, the BMAA content appears to be much higher in sharks to date. Total BMAA concentrations between 19.2 and 33.15 mg kg −1 FW were reported in fins and muscle of four shark species [ 59 ]. From this study, we only considered data of quantification performed by ultra-pressure liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) and not the one acquired by liquid chromatography with fluorescence detection (HPLC-FLD), the latter technique being less specific.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among marine taxa, the BMAA content appears to be much higher in sharks to date. Total BMAA concentrations between 19.2 and 33.15 mg kg −1 FW were reported in fins and muscle of four shark species [ 59 ]. From this study, we only considered data of quantification performed by ultra-pressure liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) and not the one acquired by liquid chromatography with fluorescence detection (HPLC-FLD), the latter technique being less specific.…”
Section: Resultsmentioning
confidence: 99%
“…The same trend is observed for marine fish in which either no BMAA or a maximum of 0.02 mg kg −1 FW of total BMAA is reported [ 50 , 54 ]. Although data mainly originate from a B graded study, it is noteworthy to mention the high BMAA contents (up to 33.15 mg kg −1 FW) reported in shark fins [ 59 ]. Moreover, a study graded A reported BMAA concentrations from 74.8 to 352.2 mg kg −1 DW in 15 out of 16 analyzed dietary supplements containing shark cartilage [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…One emerging toxin is β- N -methylamino- l -alanine (BMAA), a non-protein amino acid produced by cyanobacteria that has been linked to neurodegenerative disease, including Alzheimer’s disease (AD) and amyotrophic lateral sclerosis (ALS) [ 6 , 7 , 8 ]. BMAA can biomagnify in marine and terrestrial food chains, where it can bioaccumulate in marine apex predators and humans [ 6 , 8 , 9 , 10 , 11 , 12 ]. Exposure to BMAA causes excitotoxicity in neurons, glial activation, and tangled proteins in the brain [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…(1) The concentration of BMAA in flying foxes is indeed high relative to BMAA concentrations in most organisms from other worldwide ecosystems (e.g., Jonasson et al 2010;Brand et al 2010;Christensen et al 2012;Mondo et al 2012Mondo et al , 2014Field et al 2013;Masseret et al 2013;Al-Sammak et al 2014;Banack et al 2014Banack et al , 2015Jiang et al 2014;Réveillon et al 2016;Hammerschlag et al 2016;Scott et al 2018;Lance et al 2018).…”
Section: Misrepresentation Of the Flying Fox Hypothesismentioning
confidence: 99%
“…Follow-up studies should include even lower doses and oral exposure to identify the no observed adverse effect level (NOAEL) and further elucidate underlying mechanisms. Furthermore, Chernoff et al (2017) fail to consider co-exposure issues, e.g., individuals exposed to cyanobacterial blooms likely face more than one cyanotoxin, or in the case of simultaneous red tides and cyanobacterial blooms, multiple cyanotoxins plus brevetoxins (Metcalf et al 2020) or even methyl mercury, whose toxicity BMAA potentiates in vitro (Rush et al 2012;Mondo et al 2014;Hammerschlag et al 2016). Also, the magnitude of toxicity may be different among BMAA isomers at different ratios, e.g., BMAA is more toxic at lower concentrations than N-(2-aminoethyl)glycine (AEG) to brine shrimp (Metcalf et al 2015) while in vitro AEG is much more neurotoxic (Schneider et al 2020).…”
Section: Dosing Paradigmsmentioning
confidence: 99%